Association of Self-reported Figural Scales With Body Mass Index Among Adults With Hypertension in a Resource-limited Setting - Hong S.A. (2023)
Introduction: This study examined the performance of perceived body size in predicting measured body mass index (BMI) among adults with hypertension in Myanmar and to determine the perceived body size cutoffs for obesity. Methods: This cross-sectional study was conducted among 410 hypertensive patients attending public health centers in Myitkyina Township, Kachin State, Myanmar. Perceived body size was measured using the Stunkard’s silhouettes and was compared to a measured BMI. The performance of perceived body size was analyzed by sex-specific receiver operating characteristic curves (ROC) and the optimal perceived body size cutoffs for overweight/obesity (BMI ≥25) were determined. Results: With good correlation coefficients between perceived body size and BMI (0.78 and 0.70 in men and women respectively), perceived body size had the high area under curve (AUC) for overweight/ obesity (0.896 (95%CI=0.835-0.956) for men and 0.828 (0.761-0.895) for women). The optimal figural scales for identifying overweight/obese individuals with a correct detection rate were sixth in men and women. Linear regression analyses supported the fact that the self-reported silhouette rankings in detecting the social patterning of body size was similar with measured BMI. Conclusion: This study supports the idea that figural drawing scales are a potentially useful indicator to assess the overweight/obesity of adults in resource limit settings when self-reported and measured BMI are not available. Further studies are required to re-examine our findings and its effectiveness using a larger population.